Equalising the Levels of the Development of the Regions in the Socialist System with the Polish People's Republic as an Example - Czop, Edyta (European Journal of Sustainable Development, 2019)
After the end of World War II, the Polish authorities had to face post-war reconstruction, integrate the country's economic development within new borders, but also solve problems inherited from the Second Polish Republic: leveling civilization differences between individual regions. These issues were reflected in the plans to modernize the country, promoted by the communists. These plans contained elements of the pre-war modernization concept, but these visions were fundamentally different. The need for industrialization of backward areas proclaimed by the communist authorities was associated with political and social goals. The elimination of regional differences through balanced economic development was combined with the expansion of the working class and the elimination or marginalization of layers considered "capitalist". Additional elements, in fact playing a very large role, were the adoption of the Soviet model of modernization, which was associated with greater or lesser subordination of Moscow's goals and fulfillment of economic tasks resulting from belonging to the CMEA. The problem of sustainable development of the country was particularly strongly emphasized to half of l.50. While the country managed to integrate within the new borders, the investment policy did not reduce regional disparities. The location of new industrial plants led to disharmony in the development of Poland. The problem was also not solved in the following years. The reason was: failure of a centrally controlled economy, dominance of obsolete technologies, cyclical breakdowns in the economy, leading to socio-political crises. Keywords: Sustainable development, modernization, centrally controlled economy, investment policy, socialism